Evolution of polar nano-regions under electric field around ferro-paraelectric transition temperature and its contribution to piezoelectric property in Pb(Mg1/3Nb2/3)O3-0.30PbTiO3 crystal. Issue 15 (15th October 2018) - Wang, Rui-Xue; Zhang, Ji; Zheng, Li-Mei; Sun, Lei; Luo, Zhen-Lin; Zhang, Shan-Tao; Yang, Bin
Abstract: As one of the most pronounced structural features, polar nano-regions (PNRs) is believed to have significant contribution to the outstanding piezoelectric property of relaxor-based ferroelectrics. However, direct experimental investigation on the connection between the PNRs behavior under electric field and piezoelectric responses is still insufficient. In this work, by the combined use of piezoresponse force microscopy, polarization light microscopy, and the electrical property measurements, we investigate the structure evolution from macro-domains to PNRs around ferro-paraelectric phase transition temperature ( T m, 140 °C) in Pb(Mg1/3 Nb2/3 )O3 -0.30PbTiO3 single crystal. Most importantly, based on the corresponding analysis of unipolar strain-electric-field ( S-E ) curves at different temperatures and the direct observation of electric-field-induced structure evolution at T m, we intensively investigate the response of PNRs to electric field and its contribution to piezoelectric property. We conclude that, under electric field, the active PNRs around T m first serve as polar seeds to induce macro-domains from the non-polar matrix, then promote the switching of macro-domains. The large-field strain coefficient d 33 * in these two processes can achieve maximum of about 5410 pm/V and 61710 pm/V at T m, and gradually decreases at higher temperature with lower PNRs content.